2023
DOI: 10.3390/horticulturae9020172
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Appliance of Nano-Zeolite and Nano-Silicon Elevate Solidago canadensis Invasive Plant Tolerance to Water Deficiency

Abstract: Plant production, soil quality, and a sustainable environment depend on climate change. Drought is a multidimensional stressor that seriously affects plant production. The most sensitive plant to climate change is the invasive goldenrod (Solidago canadensis L.), which has potentially high-value materials that can be used to develop a novel approach to controlling its spread. This study aimed to evaluate the impact of different applications (NPK-chemical fertilizers (T1) as control, nano-silicon (T2), nano-NPK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…These findings could be related to the ability of the previous nano-treatments to alleviate the negative impacts of drought by enhancing hydraulic conductivity, conserving higher transpiratory and photosynthesis rates, photosynthetic pigment concentrations, and reducing oxidative damages [46,47]. Furthermore, the improvement in total carbohydrate content in drought-stressed plants supplied with N-silicon, N-zinc, and N-zeolite could be associated with elevating the photosynthesis rate and CO 2 assimilation, as shown in Figure 2D [20,41,[48][49][50]]. Pearson's correlation analysis showed that total carbohydrate content correlated positively with photosynthesis rate, intercellular CO 2 concentration, and water use efficiency (Figure 6).…”
Section: Discussionmentioning
confidence: 92%
“…These findings could be related to the ability of the previous nano-treatments to alleviate the negative impacts of drought by enhancing hydraulic conductivity, conserving higher transpiratory and photosynthesis rates, photosynthetic pigment concentrations, and reducing oxidative damages [46,47]. Furthermore, the improvement in total carbohydrate content in drought-stressed plants supplied with N-silicon, N-zinc, and N-zeolite could be associated with elevating the photosynthesis rate and CO 2 assimilation, as shown in Figure 2D [20,41,[48][49][50]]. Pearson's correlation analysis showed that total carbohydrate content correlated positively with photosynthesis rate, intercellular CO 2 concentration, and water use efficiency (Figure 6).…”
Section: Discussionmentioning
confidence: 92%
“…The onset of drought stress is influenced by a variety of factors, including variations in rainfall distribution and volume, evapotranspiration rates, and soil moisture content. In response to drought stress, plants exhibit numerous physiological stress responses, such as leaf wilting, leaf area reduction, leaf abscission, and floral drop (Bulgari et al, 2019; Othman et al, 2023; Yang and Qin, 2023). Biogenic NMs can alleviate drought stress (Giri et al, 2023), maintain plant water content, and improve plant drought tolerance by changing plant growth parameters such as dry weight and Chl content and by promoting the uptake of nutrients such as nitrogen and potassium.…”
Section: Strategies Utilizing Nps To Alleviate Abiotic Stress In Chal...mentioning
confidence: 99%
“…They can also regulate stomatal opening and closing, sugar metabolism, and photosynthesis in leaves. The research results of Othman et al (2023) indicate that under drought stress environments, the application of soil amendments mixed with nano‐silicon and nano‐zeolite‐loaded nitrogen (T5) components to climate change‐sensitive composite plants ( Solidago canadensis L.) changed the morphological traits and photosynthetic parameters (photosynthetic rate, CO 2 concentration, water use efficiency, while reducing transpiration rate). This bolstered nutrient uptake, hinting at T5's potential role in predicting the proliferation of invasive goldenrod plants under climate change or as a tactic to minimize or eradicate more harmful chemical usage.…”
Section: Strategies Utilizing Nps To Alleviate Abiotic Stress In Chal...mentioning
confidence: 99%